The Teacher Readiness Towards The Application of STEM Learning - Anjarsari, Novia; Diana, Diana (BELIA: Early Childhood Education Papers, 2020)
This study aims to determine the level of readiness of teachers towards the application of STEM learning (Science, Technology, Engineering, Mathematics) survey in kindergarten teachers in Gunungpati district, Semarang City. In addition, this study also aims to determine the supporting and inhibiting factors in the application of STEM learning in kindergarten teacher in the Gunungpati District area of Semarang City. The method is a quantitative descriptive research method with a survey design based on Singarimbun & Effendi theory. The data collection techniques using a questionnaire or questionnaire in the form of a Likert scale. The population is 116 teachers. The research sample used the Purposive Cluster Sampling design with a total sample of 25% of the total population and then fulfilled to 30 teachers. The results of the questionnaire data are collected from the whole teacher then processed and categorized based on a range of percentages. The results of the analysis of the data related to attitude and emotional readiness or Emotive-Ettitudinal Readiness, Cognitive Readiness, Behavioral Readiness. This readiness is also influenced by supporting factors such as being aware of strengths and shortcomings, adaptation, and enthusiasm. While the inhibiting factors are low cognitive knowledge and critical thinking in learning activities, perceptions, and understanding of STEM concepts that are still low and lack of discussion with other teachers and lack of cooperation with partners who are more experienced in STEM learning. In outline, this study can be concluded that teacher readiness for the application of learning STEM (Science, Technology, Engineering, Mathematics) survey in kindergarten teachers in the Gunungpati District of Semarang City has Emotive-Ettitudinal Readiness by 70% in the category of agreed or ready, Cognitive Readiness is 69.33% in the agreed or ready category, and Behavioral Readiness is 65.11% in the neutral category. This means that the readiness of teachers towards the application of learning STEM (Science, Technology, Engineering, Mathematics) in kindergarten teachers in Gunungpati District Semarang City is 68.27% in the agreed or ready category.